Melanoma brain metastases treated with stereotactic radiosurgery and concurrent pembrolizumab display marked regression; efficacy and safety of combined treatment. Issue 1 (17th October 2017) - Anderson, Erik S.; Postow, Michael A.; Wolchok, Jedd D.; Young, Robert J.; Ballangrud, Åse; Chan, Timothy A.; Yamada, Yoshiya; Beal, Kathryn
Abstract : Background: Brain metastases are common in patients with metastatic melanoma. With increasing numbers of melanoma patients on anti-PD-1 therapy, we sought to evaluate the safety and initial response of brain metastases treated with concurrent pembrolizumab and radiation therapy. Methods: From an institutional database, we retrospectively identified patients with melanoma brain metastases treated with radiation therapy (RT) who received concurrent pembrolizumab. Concurrent treatment was defined as RT during pembrolizumab administration period and up to 4 months after most recent pembrolizumab treatment. Response was categorized by change in maximum diameter on first scheduled follow-up MRI. Lesion and patient specific outcomes including response, lesion control, brain control and overall survival were recorded and descriptively compared to contemporary treatments with RT and concurrent ipilimumab or RT without immunotherapy. Results: From January 2014 through December 2015, we identified 21 patients who received concurrent radiation therapy and pembrolizumab for brain metastases or resection cavities that had at least one scheduled follow-up MRI. Eleven underwent stereotactic radiosurgery (SRS), 7 received hypofractionated radiation and 3 had whole brain treatment (WBRT). All treatments were well tolerated with no observed Grade 4 or 5 toxicities; Grade 3 edema and confusion occurred in 1 patient treated with WBRT after prior SRS. For metastases treated with SRS, at first scheduled follow-up MRI (median 57 days post SRS), 70% (16/23) exhibited complete (CR, n  = 8) or partial response (PR, n = 8). The intracranial response rates (CR/PR) for patients treated with SRS and concurrent ipilimumab and SRS without concurrent immunotherapy was 32% and 22%, respectively. Conclusions: Concurrent pembrolizumab with brain RT appears safe in patients with metastatic melanoma, and SRS in particular is effective in markedly reducing the size of brain metastases at the time of first follow-up MRI. These results compare favorably to SRS in combination with ipilimumab and SRS without concurrent immunotherapy.